Emergency preparedness for business professionals : how to mitigate and respond to attacks against your organization - Wayland, Bradley A. (Oxford, UK ; New York : Butterworth-Heinemann, an imprint of Elsevier, 2015)
Emergency Response for Business Professionals provides business managers who do not have in-house security expertise as well as the security professionals who advise them with an overview on how to prepare and react to potential unexpected incidents that can occur to their organization. The book begins with an overview of the primary principles of business emergency planning, then delves into the considerations that an organization should take when developing their emergency plan. This includes the mitigation strategies for preventing the incident from occurring in the first place. It then shows how to identify and assess the risks the organization may realistically face, choose the commensurate security measures, and create the proper emergency response policies and procedures. The book explores how to respond in the event of an actual emergency, and how to recover business operations to full functionality after an incident occurs. Emergency Response for Business Professionals looks closely at the most common emergencies that pose concerns for many organizations, such as active shooters, unauthorized visitors, workplace violence, embezzlement, fraud, theft, natural and man-made disasters, major equipment malfunctions, sabotage, labor disputes, and loss of key personnel, among others, along with the appropriate and accepted responses used to respond to each type of incident. It covers methods for training employees in emergency response, and concludes with how to plan, prepare, and conduct emergency response exercises within the organization.
Includes bibliographical references and index.
Vendor-supplied metadata.
Elsevier
Keywords: Emergency management; Business enterprises -- Security measures; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; Business enterprises -- Security measures; Emergency management; Electronic books; Electronic books